Analysis of Macroeconomic Indicators (A Case Study in North Sumatra Province) - Rahmadani Hasibuan; Muhammad Ridwan; Yusrizal (Formosa Journal of Science and Technology, 2023)
This study explores the intricate relationship between unemployment, inflation, and poverty in North Sumatra Province, Indonesia. In the second quarter of 2022, inflation surged, surpassing national and regional rates. Ali Hardana's research emphasizes inflation's impact on poverty, affecting purchasing power and wealth distribution. Methodologically, a quantitative approach using secondary data from 2010 to 2022 is employed. Panel data regression reveals economic growth's substantial influence on poverty, aligned with prior research. The study underscores Islamic economics' role in alleviating poverty, stressing justice, equitable wealth distribution, and governmental interventions. The Productive Economic Endeavors (UEP) and Non-Cash Food Assistance (BPNT) programs emerge as avenues for marginalized community upliftment, guided by social equity and economic progress. The study advocates sustained robust economic growth, equitable income distribution, and fortified social assistance programs as essential strategies to combat poverty. In essence, this study enriches comprehension of the complex ties between economic factors and poverty in North Sumatra.